Relationship of Somatotype With Static, Semi-dynamic and Dynamic Balance of Adolescent, Young and Middle-aged Women - Mahbubeh Keivan; Heydar Sadeghi (Biyumikānīk-i varzishī, 2019)
Objective Somatotype is a way of describing the human body shape and composition which can affect postural control. The aim of this study was to evaluate the relationship of somatotype with static, semi-dynamic and dynamic balances in adolescent, young and middle-aged women. Methods Participants were 140 women aged 12-50 years (Mean±SD of age=26.45±10.94) with no skeletal abnormalities, lower extremity pain and injury, vestibular and neuromuscular injury. Their anthropometric characteristics were measured and then they assigned into three groups of ectomorph (n=46), mesomorph (n=45) and endomorph (n=49) based on the heath-carter method. The Y Balance Test (YBT) was used for assessment of dynamic balance, and for semi-dynamic and static balance measurement, the Balance Error Scoring System (BESS) was used. Descriptive statistics was used to describe Mean±SD of age, height, weight, number of errors under BESS, and the reach distance in three directions under YBT. To determine the relationship of somatotype with static, semi-dynamic and dynamic balance, Chi-square test was performed considering a significance level of P≤0.05. Results Mesomorphic women had better static and semi-dynamic balance compared to the ectomorph and endomorph groups. In anterior direction under YBT, ectomorph, mesomorph and endomorph groups had the highest reach. In posteromedial direction, although endomorphs had the poorest performance, the result was not significant. In posterolateral direction, endomorphs had also the poorest performance. Conclusion Better performance of mesomorphs indicated their better muscle strength and structure which are useful for joint stability and postural control. Moreover, the better postural control of ectomorphs compared to endomorphs shows that the mass distribution of more than the height of the center of gravity until the base of support which is one of the main determinants of stability, is probably the factor that differentiated their postural control.